2015
DOI: 10.1109/lgrs.2015.2421813
|View full text |Cite
|
Sign up to set email alerts
|

Principal Component Reconstruction Error for Hyperspectral Anomaly Detection

Abstract: In this letter, a reliable, simple, and intuitive approach for hyperspectral imagery (HSI) anomaly detection (AD) is presented. This method, namely, the global iterative principal component analysis (PCA) reconstruction-error-based anomaly detector (GIPREBAD), examines AD by computing errors (residuals) associated with reconstructing the original image using PCA projections. PCA is a linear transformation and feature extraction process commonly used in HSI and frequently appears in operation prior to any AD ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…To assess the proposed method the following experiments were conducted: We first compared the proposed mitotic candidate identification phase with an alternative, principle component analysis (PCA) approach for detecting mitotic events as outliers, adapted from Jablonski et al (2015). Next, we demonstrated the clustering obtained based on the candidate daughters' symmetry and mother-daughters' dissimilarity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the proposed method the following experiments were conducted: We first compared the proposed mitotic candidate identification phase with an alternative, principle component analysis (PCA) approach for detecting mitotic events as outliers, adapted from Jablonski et al (2015). Next, we demonstrated the clustering obtained based on the candidate daughters' symmetry and mother-daughters' dissimilarity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Reconstruction-based methods Reconstruction-based methods are another set of one-class classification approaches that characterize the typical class by learning a mapping between typical input examples and a lower-dimensional representation that minimizes the loss between the input and its reconstruction from the lower-dimensional representation. PCA can be used for reconstruction-based novelty detection, in which the reconstruction error between inputs and their inverse transformation from the principal subspace is used as a novelty score (e.g., Kwak 2008;Chandola et al 2009;Toivola et al 2010;Wagstaff et al 2013;Xiao et al 2013;Jablonski et al 2015). Diaz and Hollmen (2002) used kernel-based and least-squares based general regression neural networks (GRNNs) for novelty detection and showed that kernel based approaches provided more meaningful and interpretable residuals (reconstruction errors) than least squares approaches.…”
Section: Related Workmentioning
confidence: 99%
“…Due to this reason, the impact of the compression-decompression process using just the HyperLCA transformation stage in the mentioned hyperspectral applications is evaluated and compared with the impact produced by the PCA transform for the same images and applications. It is worth to mention here that the PCA transform is used in many hyperspectral applications, such as unmixing or classification, for spectrally decorrelating the information and reducing the number of spectral components of the data set, with the goal of reducing the redundant information, increasing the separability of the different elements of interest and improving the application results [9,10,27]. Accordingly, the PCA transform can be considered as a good reference to compare with, regarding the impact of the HyperLCA transform in the ulterior hyperspectral applications.…”
Section: Evaluation Of the Impact Produced By The Hyperlca Compressiomentioning
confidence: 99%